Cálculo de regra de três e proporcionalidade com aplicação na dosimetria no direito do apenado - CAVALCANTE, Elielson Piteira (2022)
This course conclusion work presents a discussion about mathematics in the law of the convict, that is, it shows an overview of the discipline in the life of the convict until his freedom. It highlights the interdisciplinarity of Law and Mathematics and the relationship in the right to punish conferred on the State. It is also noteworthy that in Brazil compared to the United States of America in the mathematical bias and its (in) effectiveness as a speedy strategy in the criminal process. Mathematical knowledge is perceived in the decisive role in the life of an individual in the process, including the need to insert mathematics content in the curriculum of the law course, for better preparation of the legal professional with some difficulty in facing the challenge of understanding the law. Mathematics included in Law before the profession. The research concludes considering that mathematics as a science has relevance in the area of law, serving as a basis for equating and determining the right time according to the sentence and the progression of the convict.